The impact of a package of behaviour change interventions on breastfeeding practices in East Java Province, Indonesia. Issue 3 (29th April 2022) - Titaley, Christiana Rialine; Dibley, Michael J.; Ariawan, Iwan; Mu'asyaroh, Anifatun; Paramashanti, Bunga Astria; Alam, Ashraful; Damayanti, Rita; Do, Tran Thanh; Ferguson, Elaine; Htet, Min Kyaw; Li, Mu; Sutrisna, Aang; et al.
Abstract: Suboptimal infant young child feeding practices are frequently reported globally, including in Indonesia. This analysis examined the impact of a package of behaviour change interventions on breastfeeding practices in Malang and Sidoarjo Districts, East Java Province, Indonesia. The BADUTA study (which in the Indonesian Language is an acronym for BAwah DUa TAhun, or children aged less than 2 years) was an impact evaluation using a cluster‐randomized controlled trial with two parallel treatment arms. We conducted household surveys in 12 subdistricts from Malang and Sidoarjo. We collected information from 5175 mothers of children aged 0–23 months: 2435 mothers at baseline (February 2015) and 2740 mothers at endline (January to February 2017). This analysis used two indicators for fever and diarrhoea and seven breastfeeding indicators (early initiation of breastfeeding, prelacteal feeding, exclusive breastfeeding under 6 months, predominant breastfeeding, continued breastfeeding, age‐appropriate breastfeeding and bottle‐feeding). We used multilevel logistic regression analysis to assess the effect of the intervention. After 2 years of implementation of interventions, we observed an increased odds of exclusive breastfeeding under 6 months (adjusted odds ratio [aOR] = 1.85; 95% confidence interval [CI]: 1.35–2.53) and age‐appropriate breastfeeding (aOR = 1.39; 95% CI: 1.07–1.79) in the intervention group than in the comparison group, at the endline survey. We found significantly lower odds for prelacteal feeding (aOR = 0.52; 95% CI: 0.41–0.65) in the intervention than in the comparison group. Our findings confirmed the benefits of integrated, multilayer behaviour change interventions to promote breastfeeding practices. Further research is required to develop effective interventions to reduce bottle use and improve other breastfeeding indicators that did not change with the BADUTA intervention. Abstract : This analysis examined the impact of a package of behaviour change interventions on breastfeeding practices in Malang and Sidoarjo Districts, East Java Province, Indonesia. We used information from 5175 mothers of children aged 0–23 months interviewed in this study. After 2 years of implementation of interventions, we found an increased odds of exclusive breastfeeding under 6 months and age‐appropriate breastfeeding in the intervention group than in the comparison group. We also found significantly lower odds for prelacteal feeding in the intervention group than in the comparison group. Key messages: The integrated package of behaviour change interventions in the BADUTA study (which in the Indonesian Language is an acronym for BAwah DUa TAhun, or children aged less than 2 years) increased exclusive and age‐appropriate breastfeeding practices in children under 2 years old in Indonesia. The BADUTA study interventions did not significantly affect early breastfeeding initiation, breastfeeding in the last 24 h, ever breastfed, continued breastfeeding, predominant breastfeeding, bottle‐feeding practices, fever and diarrhoea 2 weeks before the interview. Further research is required to develop effective interventions to improve continued breastfeeding after 12 months of age and reduce predominant breastfeeding for children aged 0–5 months and bottle‐feeding practices.